2010
DOI: 10.1007/s10336-010-0627-4
|View full text |Cite|
|
Sign up to set email alerts
|

Shell thickness and pore density in relation to shell colouration, female characteristics, and environmental factors in the Collared Flycatcher Ficedula albicollis

Abstract: Avian eggshell structure may have important consequences for embryonic growth and development, but relatively little is known about the factors responsible for variation in eggshell characteristics of wild birds. In this paper, we explored potential causes of variation in eggshell colour and structure (shell thickness and porosity) in the Collared Flycatcher (Ficedula albicollis). We analysed if eggshell colour is affected by shell structure or pigment level, and whether female traits, laying date, local breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 72 publications
3
19
0
7
Order By: Relevance
“…This foraging flexibility of Great Tits could possibly be the reason why we found that environmental conditions had no significant effect on eggshell thickness. Our results are in concordance with previous findings, as eggshell thickness also did not vary with laying date and ambient temperature in other bird species (Eeva and Lehikoinen 1995;Massaro and Davis 2004;Hargitai et al 2011;Stein and Badyaev 2011).…”
Section: Breeding Density (Pair/100 M Radius Circle)supporting
confidence: 95%
“…This foraging flexibility of Great Tits could possibly be the reason why we found that environmental conditions had no significant effect on eggshell thickness. Our results are in concordance with previous findings, as eggshell thickness also did not vary with laying date and ambient temperature in other bird species (Eeva and Lehikoinen 1995;Massaro and Davis 2004;Hargitai et al 2011;Stein and Badyaev 2011).…”
Section: Breeding Density (Pair/100 M Radius Circle)supporting
confidence: 95%
“…This finding is in accordance with recent investigations of the ability of other non‐pigment‐based factors to drive variation in eggshell coloration, including eggshell smoothness (Igic et al ) and cuticle properties (Fecheyr‐Lippens et al ). More specifically, the importance of eggshell thickness in explaining variation in coloration has been documented in pied flycatchers Ficedula hypoleuca (Morales et al ), although no effect was detected in collared flycatchers Ficedula albicollis (Hargitai et al ) or spotless starlings Sturnus unicolor (López‐Rull et al ). However, these studies, in addition to the work presented here, relied upon light that is reflected off the eggshell to quantify coloration.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of pigmentation did not significantly affect shell thickness and water vapour conductance values for samples of shell pieces from either the speckled or plain areas did not differ significantly. Similarly, in the collared flycatcher (Ficedula albicollis) neither shell thickness nor pore density are affected by variability in shell colouration as measured in the blue-green or UV chroma (Hargitai et al, 2011).…”
Section: Wild Bird Speciesmentioning
confidence: 93%